ANALISA E-CONOMY DI ASEAN (Studi Komparatif di Enam Negara ASEAN) - Jati Imantoro; Karnila Ali (FIDUSIA : JURNAL KEUANGAN DAN PERBANKAN, 2019)
This study aims to analyze the development of e-conomy in ASEAN in terms of population use, capitalization value, e-conomy growth, consumer motivation in internet use, and fintech. This research uses descriptive qualitative by using comparative and qualitative methods, namely comparing a debate and analyzing data and matters relating to the numbers used to analyze the problem being carried out. The sample in this study was six ASEAN countries containing Thailand, Vietnam, Singapore, Indonesia, Philippines and Malaysia. E-conomy is getting faster and faster, faster and faster can make money through the internet, growth opportunities outside Metros, and Financial Technology using the era of disruption. Keywords: E-conomy, ASEAN, Financial Technology, Growth